Analisis Pemberdayaan Kelompok Perempuan Nelayan Berbasis Digital Mother School Dalam Mendukung Pembelajaran Daring - Mikael Irwan S Surumaha; Beby Masitho Batubara; Nina Angelina (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
The purpose of this study was to determine the process of empowering women fishermen groups based on digital mother school in supporting online learning in bawolowalani village south nias regency. The teory used in this reseach is Nursahbani Katjasungkana, namely the existence of acces in the sense of equal rights in accesing productive resource in the environment, participation, control, and benefits. The research method used is qualitative where by means of observations, interviews, and documentation. The empowerment of women fishirmen groups based on digital mother school in supporting online learning carried out in bawolowalani village went very while the activities carried out such as giving lessons related to basics of science and tecnhnology through manuals, various online application, teaching people how to operated android phones. So that people are smart and can acces online aplications and used them for publich and personal interest. However, the procces turned out to be not running optimally because some people do not have android phones, the distance is long because the village of Bawolowalani consist of five hamlets, constrained by working time and homework so that some of these weaknesses are a problem in the procces of empowering fisherwomen group based on digital mother school in supporting online learning in Bawolowalani village.